Pengembangan Kewirausahaan Pedesaan : Upaya Peningkatan Kemandirian Komunitas - Ima Kristina Yulita; Ferrynela Purbo Laksono (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Business owners in the village of Bluder, Kemuning and Plosokerep are still experiencing difficulties in developing their business, so they need to gain knowledge about entrepreneurship and are invited to discuss and share with fellow business owners to be excited again in managing their business. The purpose of this training is to provide knowledge about entrepreneurship holistically. The method used is classical discussion and group discussion. The result of this service is that the participants understand more about the concept of entrepreneurship, especially regarding pricing and promotion, and are more enthusiastic in continuing their business. The discussion result show that they have difficulty setting prices. Their tendency to set prices too high because they feel that all goods produced can be marketed through tourist attractions. The reality is not so, they find it difficult to sell the goods that have been produced.